The artistic path to virtue - Sher, Gavin (Rhodes University, Faculty of Humanities, Department of Philosophy, 2007)
Most people share a strong intuition that there is much to be learned from great literature and other forms of narrative art. This intuition is, however, philosophically contentious. Plato was the first to argue against the possibility of learning anything from narrative art, but he founded a tradition that persists to the present day. I will engage in this debate in order to examine the role narratives might be able to play in acquiring virtue on Aristotle's ethical account, as it is presented in Nicomachean Ethics. I will claim that narratives have so long seemed a problematic source of learning because philosophers have traditionally approached the issue in the wrong way. They have typically tried to show how we might acquire propositional knowledge through our engagement with art, but this approach has failed because of insoluble problems involved in satisfying the justification criterion. Fictions may be rescued from their problematic status by realising that what we truly get from them is, instead, a type of knowledge-how. I will argue that Aristotelian virtue is itself a kind of knowledge-how and so the type of learning that takes place in engaging with narratives has a role to play in its acquisition and exercise. Virtue depends on types of reasoning that are themselves kinds of knowledge-how and which are employed and improved in engaging with narrative art. These types of reasoning will be described as conceptual, emotional and imaginative understanding. I will show how each is important in relation to virtue and how each is a kind of knowledge-how that may be improved through exposure to narrative art.
Keywords: Aristotle -- Nicomachean ethics; Virtue; Ethics; Fiction; Narration (Rhetoric)